2014
DOI: 10.1002/acp.3005
|View full text |Cite
|
Sign up to set email alerts
|

The Weapon Focus Effect in Target‐Present and Target‐Absent Line‐Ups: The Roles of Threat, Novelty, and Timing

Abstract: SummaryWhen an eyewitness suffers an impairment of memory for a perpetrator because the criminal used a weapon during the crime, this impairment is called the weapon focus effect. The literature is split on how this arises: Some implicate the narrowing of attentional cues to the weapon because the arousal of the victim increases, whereas others claim that the weapon is a novel object in most everyday contexts, and novel objects demand more attention than contextually appropriate ones. The current study employe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(38 citation statements)
references
References 40 publications
2
36
0
Order By: Relevance
“…These results are consistent with previous studies that have shown a negative effect of an unexpected event on EM. 18,19,26,27 The present study has some limitations. First, we measured emotional arousal using self-reporting measures.…”
Section: Discussionmentioning
confidence: 84%
“…These results are consistent with previous studies that have shown a negative effect of an unexpected event on EM. 18,19,26,27 The present study has some limitations. First, we measured emotional arousal using self-reporting measures.…”
Section: Discussionmentioning
confidence: 84%
“…Historically, the effect on eyewitness identification has been less robust (e.g., Kramer et al, ; see meta‐analysis by Fawcett, Russell, Peace, & Christie, ). However, four experiments have recently found that eyewitness identification accuracy does indeed decline for crimes involving a weapon (Carlson & Carlson, , ; Carlson, Dias, Weatherford, & Carlson, in press; Erickson, Lampinen, & Leding, ). Two of these will be discussed in greater detail below.…”
Section: Exposure Time To the Perpetratormentioning
confidence: 99%
“…Erickson et al () addressed many of these limitations (see also Carlson & Carlson, , ). They conducted a large ( N = 1263; about 70/cell) experiment involving the timing of a neutral object (empty glass), unusual object (rubber chicken), or weapon (fake but realistic‐looking gun) during a slide presentation.…”
Section: Exposure Time To the Perpetratormentioning
confidence: 99%
See 1 more Smart Citation
“…However, the strongest evidence of weapon focus is confined to laboratory studies in which participants are shown a mock‐crime (either live or via video or slideshow) that they are later questioned about. Participants who witness a scene featuring an armed perpetrator tend to remember this person less accurately than those shown a matched scene in which he was unarmed (e.g., Carlson, Dias, Weatherford, & Carlson, ; Cutler, Penrod, O'Rourke, & Martens, ; Cutler, Penrod, & Martens, , ; Erickson, Lampinen, & Leding, ; Loftus et al, , Experiment 2; Pickel, ; Tooley, Brigham, Maass, & Bothwell, ). Although there is evidence that arousing stimulus scenes restrict the attentional focus of participants on to the most central features impairing memory for peripheral scene features (Christianson, ; Davies, Smith, & Blincoe, ), it is unlikely that the levels of participant arousal elicited by mock crimes shown in lab studies are anywhere near as high as those experienced by witnesses of real armed crimes (Kocab & Sporer, ).…”
Section: Introductionmentioning
confidence: 99%